The library space as a center of the cultural life of Leningrad citizens in the 1950s - early 1960s - F. K. Yarmolich (Библиосфера, 2017)
The article is devoted to a tool for including Leningrad citizens in the socio-political and cultural context of the USSR development. The article objective is to demonstrate the mechanism and forms of this process on materials of Leningrad libraries. To achieve this goal, a number of tasks are being accomplished. First, the library space system has been recreated, which included city, district, garden and park and other types of libraries. Secondly, the library activity forms are described. Third, attention is focused on a differentiated approach to work with different categories of citizens. The article is based on archival material collected in three archives of St. Petersburg. To create an objective picture of Leningrad realities in the 1950s - early 1960s several categories of documents were used: reporting documentation, correspondence, minutes of party and production meetings. The combination of such groups, different in their information content of documents, allowed criticizing sources, revealing information that reflected the point of view of the institution and to some extent changed realities of the 1950s - early 1960s, etc.